HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN IBU MENYUSUI DENGAN PEMBERIAN SUSU FORMULA PADA BAYI UMUR 0-6 BULAN DI WILAYAH KERJA PUSKESMAS II PURWOKERTO UTARAKABUPATEN BANYUMAS - Susilo - Rini (Universitas Harapan Bangsa Purwokerto, 2009)
According to Indonesia Demographic and Health Survey in 2008, the consumptionof formula milk in Indonesia had increased from 15% in 2003-2004 to 30% in 2008. Tthecomplications that occur in babies feed with formula, among other things the risk ofcontamination so that the baby has infected the gastrointestinal and respiratory , failure togrowth and risk of overweight (obesity).The purpose of this research is to determine the effectof the characteristics and knowledge of breastfeeding mothers to formula feeding at infantaged 0-6 months. The type of this research is explanatory, with cross sectional approach. Thesampling technique was done by random sampling with 51 respondents. The test statistic used is Chi Square. The result of this research from the total of 51respondent is 46 respondents give formula to infants aged 0-6 months27 (52.9%), respondents are high school graduate 22(43.1%), respondents have a job as PNS/Police 46(90.2%) respondents. The conclusions of this research show that related factors are theknowledge. Factors that are not related is the characteristic of age. Key words: Milk formula, Characteristics, Knowledge.